Optimizing Branding and Digital Marketing for the Bamboo Weaving Home Industry in Puntukdoro Magetan - Muh. Maksum; Chairul Rizki; Arum Merry Ringgani; Linda Nur Hamidah (JARDIRA – Jurnal Pengabdian Digital dan Rekayasa Informatika, 2026)
ABSTRACT Background: Bamboo weaving crafts in Ngelo Hamlet, Puntukdoro Village, Magetan Regency, are a cultural heritage that has developed over a long period of time and has become the main source of livelihood for the local community. Despite their high aesthetic and functional value, the marketing system used is still traditional and dependent on intermediaries, resulting in low selling prices and limited market reach. This situation highlights the need for community empowerment strategies that can optimize local assets through digital-based marketing and branding approaches. Contribution: This program contributes to the development of an Asset Based Community Development (ABCD) model that is integrated with digital marketing and village branding. In addition to strengthening the identity of Ngelo Hamlet as the “Bamboo Weaving Village,” this program also provides practical digital marketing skills to artisans that can be replicated in similar craft communities. Method: This community service program was implemented using the ABCD approach through five stages, namely inculturation, discovery, design, define and reflection. The main activities included digital marketing training, branding development, and promotional media production. Social media platforms such as Instagram, TikTok, and YouTube were used as the main marketing tools, supported by the production of a village profile video titled Cakrawala Puntukdoro. Results: The program results show an increase in artisans' awareness and understanding of digital marketing, expanded product exposure to a wider market, and the beginning of direct interaction between artisans and consumers. However, limited digital literacy and the short duration of assistance remain major challenges. Conclusion: The integration of branding and digital marketing based on the ABCD approach has been proven to increase the competitiveness and economic potential of the bamboo weaving home industry in Puntukdoro Village. Continuous support from the village government, academics, and business actors is needed to ensure the long-term impact and sustainability of local economic development